Understanding MeJA induced-resistance to Phytophthora cinnamomi in holm oak embryogenic lines - Morcillo, Marian; Sanchez-Lucas, Rosa; Sales, Ester; Jorrín-Novo, Jesús; Miedes, Eva; Arrillaga, Isabel (Frontiers in Plant Science, 2026)
Holm oak (Quercus ilex L.) decline in Mediterranean forests is mostly driven by the synergistic effects of drought and Phytophthora cinnamomi, yet effective protection strategies remain elusive. Previously, we reported that elicitation of holm oak embryogenic lines with 50 µM methyl jasmonate (MeJA), did not impair somatic embryo growth and development while inducing jasmonic acid (JA) and phenolic compounds accumulation, also resulting in increased H2O2 levels and further JA production after challenged against active oomycete mycelium. Here, we evaluate the proteomic profile in the E00 embryogenic line of Q. ilex in response to this priming treatment and subsequent pathogen inoculation. To this end, embryogenic cultures were first treated with a solution of 0 or 50 µM MeJA for three days and five days later, inoculated or not with a P. cinnamomi mycelia extract. Twenty-four hours post-inoculation, samples were harvested, proteins extracted from the four treatments, and analysed by nano-LC-MS/MS on an Orbitrap Fusion. SEQUEST searches against a translated Q. ilex transcriptome identified 3,205 protein species with high confidence. Multivariate sparse PLS-DA captured 68.9% of variance and clearly discriminated between treatments, particularly separating inoculated from non-inoculated samples. MeJA elicitation led to the accumulation of proteins associated with cell-wall biogenesis, carbon metabolism, and amino-acid and phenylpropanoids biosynthesis. Some of these proteins were also accumulated, but to a lesser extent, by pathogen inoculation in non-elicited cultures. Notably, 24 hours after inoculation, MeJA – elicited samples showed enhanced abundance of proteins hormone-signalling and redox enzymes, including cinnamate-4-hydroxylase, caffeoyl-CoA O-methyltransferase, glutathione S-transferases, calreticulin, thaumatin-like proteins, catalase and chitinase. These results revealed that MeJA elicitation induced a primed state in Q. ilex embryogenic lines, reprograming the proteome to enhance early defence and oxidative stress response pathways upon P. cinnamomi e inoculation. This supports MeJA priming as a promising biotechnological strategy to improve holm oak resilience and productivity complementing integrated pest management and breeding strategies.